Semiconductor-Optical-Amplifier Mach-Zehnder Interferometer Based Optical Networks - Vinai K. Singh; Ajit Kumar Singh Yadav; Ajay Kumar; Anand Tyagi (Institute of Advanced Engineering and Science, 2013)
In this paper, an all-optical AND logic scheme which exploits the cross-phase modulation (XPM) effect in semiconductor-optical-amplifier-assisted Mach-Zehnder Interferometer (SOA-MZI), is proposed, performance analyzed and parameters optimized. The proposal is validated and the system performance under various parameters is examined through numerical simulations. With only moderate parameters, high-speed all-optical AND gate based on SOA-MZI is realized with fairly high performance. The results are helpful for designing of SOA-based all-optical logic devices. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1926